Effects of hormonal contraception on vocal patterns of captive southern yellow-cheeked gibbons (Nomascus gabriellae) - Hradec, Michal; Bolechová, Petra; Vostrá-Vydrová, Hana (Frontiers in Veterinary Science, 2025)
The effects of hormonal contraception in non-human primates have been studied predominantly in relation to reproductive physiology. To date, no study has investigated how hormonal contraception affects vocal patterns in non-human primates. As part of our long-term research into the vocal behavior of southern yellow-cheeked gibbons (Nomascus gabriellae) in zoos, we have managed to obtain vocal datasets from four adult contracepted (Nexplanon® and Depo-Provera®) females of this species. In addition, we also recorded coda vocalizations (i.e., male calls added after the completion of the great call) from three paired males who are partners of three of the four females studied. We quantified 11 acoustic features in the female great calls and five acoustic features in the male coda vocalizations, for which we applied a Principal Component Analysis (PCA) and subsequently components were tested using multivariate Generalized Linear Mixed Models (GLMM). Our study revealed that hormonal contraception did indeed affect the vocal structure of great call in southern yellow-cheeked gibbon females. In contrast, our study did not reveal any flexible adjustment of the structure of the coda vocalization in direct response to changes in the females’ song. In female great call, we found that the Group 1 call component and Group 2 call component were not affected by the hormonal contraceptive (Depo-Provera®) in the during-application period. However, it was noteworthy that once the effects of contraception had worn off (post-application period), the values of components did not return to pre-application periods but continued to change. Conversely, although the values of the Group 1 call component and Group 2 call component were most greatly affected by the contraceptive Nexplanon® (during-application period). The values of both components tended to return to pre-treatment levels once the effects had waned. There was a change in the values of the Group 3 call component only after application of the contraceptive Nexplanon®. These values remained significantly higher than the values at the pre-application level once the effects waned. This study provides the first evidence of changes in the stable vocal patterns of female southern yellow-cheeked gibbons as a consequence of the application of hormonal contraception.